G-Protein-Coupled Inwardly Rectifying Potassium (GIRK) Channel Activation by the p75 Neurotrophin Receptor Is Required for Amyloid β Toxicity - May, Linda M.; Anggono, Victor; Gooch, Helen M.; Jang, Se E.; Matusica, Dusan; Kerbler, Georg M.; Meunier, Frederic A.; Sah, Pankaj; Coulson, Elizabeth J. (Frontiers in Neuroscience, 2017)
Alzheimer's disease is characterized by cognitive decline, neuronal degeneration and the accumulation of amyloid-beta (Aβ). Although the neurotoxic Aβ peptide is widely believed to trigger neuronal dysfunction and degeneration in Alzheimer’s disease, the mechanism by which this occurs is poorly defined. Here we describe a novel, Aβ-triggered apoptotic pathway in which Aβ treatment leads to the upregulation of G-protein activated inwardly rectifying potassium (GIRK/Kir3) channels, causing potassium efflux from neurons and Aβ-mediated apoptosis. Although GIRK channel activity is required for Aβ-induced neuronal degeneration, we show that it is not sufficient, with coincident signaling by the p75 neurotrophin receptor (p75NTR) also required for potassium efflux and cell death. Our results identify a novel role for GIRK channels in mediating apoptosis, and provide a previously missing mechanistic link between the excitotoxicity of Aβ and its ability to trigger cell death pathways, such as that mediated by p75NTR. We propose that this death-signaling pathway contributes to the dysfunction of neurons in Alzheimer's disease and is responsible for their eventual degeneration.